2016
DOI: 10.1038/srep28991
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Response is Driven by UCS Revaluation: Evidence, Neurophysiological Consequences and a Quantitative Model

Abstract: Despite growing scientific interest in the placebo effect and increasing understanding of neurobiological mechanisms, theoretical modeling of the placebo response remains poorly developed. The most extensively accepted theories are expectation and conditioning, involving both conscious and unconscious information processing. However, it is not completely understood how these mechanisms can shape the placebo response. We focus here on neural processes which can account for key properties of the response to subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…In practice we argue that the overall response induced within the CNS is always determined by an active (energy based) and a reactive (pure information) contribution, and that the brain cannot discriminate between these two quantities during the response (or outcome) evaluation. This fact could also represent the basis of the placebo induced response (Puviani and Rama 2016 ).…”
Section: Methodsmentioning
confidence: 94%
“…In practice we argue that the overall response induced within the CNS is always determined by an active (energy based) and a reactive (pure information) contribution, and that the brain cannot discriminate between these two quantities during the response (or outcome) evaluation. This fact could also represent the basis of the placebo induced response (Puviani and Rama 2016 ).…”
Section: Methodsmentioning
confidence: 94%
“…Placebo effects mediate a variety of processes, including learning, anticipation, and social cognition, and can affect a variety of clinical and physiological outcomes related to health (Wager and Atlas, 2015). It has also been shown that the placebo response can be conceptualized as the reaction of a distributed neural system within the central nervous system (Puviani and Rama, 2016). Finally, the placebo effect comes from the psychosocial forces surrounding the patient and the treatment, not the contrived practices themselves (Zion and Crum, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In fact, provided that theoretical models for non-conscious (i.e., implicit) emotional processing are available [some developments at a preliminary stage can be found in Ref. (12, 52, 53; Puviani et al, under review 1 )], theoretically meaningful parameters can be extracted; such parameters can then be used as efficient, low-dimensional representations of the very high-dimensional data to which ML techniques for classification or regression can subsequently be applied. Moreover, the inherently reduced dimensionality improves the generalization of diagnostic (i.e., classification or regression) algorithms, partially prevents overfitting and reduces the number of patients needed in a training stage (50).…”
Section: A Computational Diagnostic Tool Based On the Variations Of Nmentioning
confidence: 99%